User-centered Design dalam Membangun Desain Aplikasi Dewan Masjid Indonesia (DMI) Kota Semarang berbasis Web - Nurul Anisa Sri Winarsih (Jurnal Ilmu Komputer, 2020)
Indonesia is the country with the largest Muslim population in the world where the Muslim population in Indonesia reaches 88% of the total population. Thus, Indonesia will also have many mosques as places of worship for Muslims. The management of the mosque is mostly carried out by a group of local volunteers and each mosque has a board of directors whose task is to manage administrative matters. Some difficulties arise, among others, the mosque management did not get direction from the central mosque observer board on how to manage the mosque's potential, consequently this potential management was not well-managed. Therefore, we made a website-based information management application. The application is useful for managing all information about the management of a mosque in the city of Semarang as a support service provided to the community to improve their standard of living through the sale of pilgrim products and the management of mosque activities. This website design will follow the User-Centered Design approach, where designing an interface design that focuses the user as the main role in determining system requirements. The interface design of a system can follow the usability goal and user experience guidelines. Usability produces a system that is useful, effective, easy to learn, and easy to remember. In addition, user experience makes users feel helped and interested.